Screening and Validation of Leaf Width-Related Genes in Inbred Maize Lines - Shi Lu; Qi Wang; Junqi Yin; Shubo Zheng; Tingting Gao; Xudong Zhou; Jianxin Zhang; Yuexian Xing; Yingjie Ma; Min Wang; Delong Zhou; Ming Lu; et al. (Life)
Leaf width is a key determinant of planting density and photosynthetic efficiency. In an effort to determine which genes regulate maize plant leaf width, we performed a genome-wide association study (GWAS) of 1.49 × 106 single nucleotide polymorphisms (SNPs) in 80 sequenced backbone inbred maize lines in Jilin Province, China, based upon phenotypic leaf width data from two years. In total, 14 SNPs were identified as being significantly related to leaf width (p < 0.000001), with these SNPs being located on chromosomes 1, 2, 3, 5, 6, 7, 8, and 9. A total of five candidate genes were identified within a mean linkage disequilibrium (LD) distance of 9.7 kb, with a significant SNP being identified within the Zm00001d044327 candidate gene. RNA was then isolated from 12 different inbred maize lines from this GWAS study cohort and was used to conduct qPCR analyses which revealed significant differences in Zm00001d044327 expression among strains exhibiting significant differences in leaf width. Based on an assessment of EMS mutant lines harboring a conserved amino acid stop mutation and two non-synonymous mutations in Zm00001d044327 that exhibited a narrow leaf width, these data suggested that Zm00001d044327 is a key regulator of maize leaf width.